DYSLEXIA AND EFL TEACHING AND LEARNING: A CASE STUDY IN BALI CHILDREN FOUNDATION, SINGARAJA-BALI - Kusuma Dewi, Ketut Mirani (Jurnal Pendidikan Bahasa, 2012)
DYSLEXIA AND EFL TEACHING AND LEARNING: A CASE STUDY IN BALI CHILDREN FOUNDATION, SINGARAJA-BALI by Ketut Mirani Kusuma Dewi This research was conducted in an attempt to give general overview how dyslexia influence students in learning English as Foreign Language, dyslexic studentsâ responses in Innovative Teaching Method provided by teacher and the performance of dyslexic students in the four language skills. The subjects of this research were students of Bali Student Foundation (Yayasan Samiarsa Seminyak) class VI & VII who were confirmed dyslexic by Youth Shine Academy using Dyslexia Screening Test. By using European Language Portfolio, Classroom observation and teacherâs note, the researcher observed dyslexic students in EFL learning and narrated using case study report. Based on the data analysis, the study identified some findings.First, each dyslexic student displays a different set of features, but there is one common problem all dyslexics face - it is difficulty with the written language, a failure to recognize and interpret what is perceived. Dyslexia is a problem that many students face and have great difficulty coping with in a school environment. However, with the help and support of the teacher, dyslexic students can become successful learners. The role of teachers is to make educational adjustments to facilitate learning and create successful class environment. Some improvements have been obtained by dyslexic students using Innovative Teaching Methods with different time accumulation depend on complexity of their problems. The dyslexic students perform better in Speaking and Listening rather than in Writing and Reading but by time and strategy they can show improvement in Writing and Reading. Â  Â  Key words: EFL teaching & Learning, Dyslexia and EFL DISLEKSIA DAN PEMBELAJARAN EFL: STUDI KASUS DI BALI CHILDREN FOUNDATION, SINGARAJA-BALI oleh Ketut Mirani Kusuma Dewi Â  Penelitian ini dilakukan untuk memberikan gambaran umum bagaimana pengaruh disleksia pada siswa dalam pembelajaran Bahasa Inggris sebagai Bahasa Asing, tanggapan siswa disleksia dalam Metode Pengajaran Inovatif yang diberikan oleh guru dan kinerja siswa disleksia dalam empat keterampilan berbahasa. Subyek penelitian ini adalah siswa dari Bali Children Foundation (Yayasan Samiarsa Seminyak) kelas VI & VII yang dikonfirmasi disleksia oleh Youth Shine Academy menggunakan Uji Disleksia. Dengan menggunakan European Language Portfolio, observasi Kelas dan catatan guru, peneliti mengamati siswa disleksia di pembelajaran EFL dan melaporkan dengan menggunakan studi kasus. Setiap penderita menampilkan gejala yang berbeda, tapi masalah umum anak dysleksia - adalah kesulitan dengan bahasa tertulis, kegagalan untuk mengenali dan menafsirkan apa yang dirasakan. Disleksia adalah masalah kesulitan belajar yang banyak siswa hadapi dan alami dalam lingkungan sekolah. Namun, dengan bantuan dan dukungan dari guru, siswa disleksia dapat menjadi pelajar yang sukses. Peran guru adalah melakukan penyesuaian untuk memfasilitasi pembelajaran dan menciptakan lingkungan kelas yang sukses. Beberapa perbaikan telah didapat oleh siswa disleksia menggunakan Metode Pengajaran Inovatif dengan akumulasi waktu yang berbeda tergantung pada kompleksitas masalah mereka. Para siswa disleksia tampil lebih baik dalam Berbicara dan Mendengarkan bukan di Menulis dan Membaca tetapi dengan waktu dan strategi mereka dapat menunjukkan perbaikan dalam Menulis dan Membaca. Â  Kata kunci: Pembelajaran EFL, Dyslexia and EFL